(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
This study was conducted in the ruminant field of the Animal Production Department/ College of Agriculture/ Diyala University. And the animals were in good health, the field experiment period lasted from 10/6/2022 to 10/9/2022 (for a period of three months), after which the animals were slaughtered and testicles were collected to take the required measurements in the experiment, and 16 adult male Afghan goats were used in this study Sexually, their ages range from 1-1.5 years, and their weight ranges between (35-40) kg. The study animals were randomly divided into four groups, with four replicates for each group. The difference in male weights ranged from 1.5-2.5 kg in one group. The first group was left without vaccination ( control group), while the other three groups were dosed with different concentrations of the amino acid tyrosine (Tyrosin_L) every 48 hours, namely: the second group was dosed with 50 mg of tyrosine / kg of body weight, the third group was dosed with 75 mg of tyrosine / kg of body weight, and the fourth group was dosed with 100 mg Tyrosine / kg of body weight. At the end of the experiment, the animals were slaughtered and the right testis was taken for measurement and preserved in formalin at a concentration of 10% until the measurement of the dominant sex cells (Sertoli cells, Leydec cells and spermatogenic cells) required in the study. The results showed that the dose of the amino acid tyrosine led to a highly significant increase (P≤0.01) in the number of Sertoli cells, Ledec cells, and spermatogenic cells in the third and fourth dose treatments, compared to the second and first doses (control group). Therefore, we recommend the possibility of dosing tyrosine acid in male Afghani goats outside the reproductive season to stimulate them sexually.